Undersea gliders - Griffiths, G; Jones, CP; Ferguson, IJ; Bose, N (2007)
Undersea gliders offer a unique alternative to autonomous underwater vehicle (AUV) propulsion through the use of buoyancy change and wings, as propulsive power is generally the largest component of an underwater vehicle's electrical power draw. This approach affords the opportunity for long term endurance. With operations at slow speed (<0.5 m.s-1) and extremely frugal use of the electrical power available within the vehicle (typically less than 1 W on average), very long endurance can be achieved (over six months, or 3000 km). Two-way satellite communications, allow gliders to send data ashore and receive new mission commands, enabling powerful new concepts in ocean data collection. So far, Glider missions have concentrated on gathering data in support of biological and physical oceanography. They have contributed to studies on ecosystem dynamics, algal blooms, ocean circulation and climate-related research. Operations have taken place in regions from the Arctic through the tropics, in the face of a variety of hazards including sea ice, hurricanes and vessel traffic. Advances in technology should enable next-generation undersea gliders to travel further and dive deeper. Gliders can also be expected to carry more advanced payloads allowing them to act in more intelligent and cooperative ways.